Labor Issues that the H2A Temporary Agricultural Worker Policy Attempts to Resolve in Florida - Jonathan C. Stephens; John Lai; Bachir Kassas (EDIS)
Labor is a critical component of a successful agricultural venture. In 2020, the USDA reported that 10.3% of total US employment was in jobs in the agricultural and food sectors. We rely on food, fiber, and natural resources, and effective agricultural labor is a critical social need, but the challenges inherent in the effort to secure agricultural labor are many and difficult to solve. Particularly in Florida, maintaining a labor sufficient to meet the needs of the industry presents a complex problem. Controversies abound over issues like human rights and migrant vs. domestic labor. Today the H-2A Temporary Agricultural Workers Program is providing some compromise and progress within the agricultural labor crisis. The purpose of this publication is to review agricultural labor in Florida and  analyze how the H-2A program addresses agricultural labor challenges. The publication will be of interest to consumers, labor activists, producers, corporations, and governments.